The Determinants of FDI in the Manufacturing Industry in China - Case Studies of Taiwanese SMEs - Chao, Pin-Ching (2011)
Due to the trend of economic globalisation and Taiwan’s deteriorating business environment, Taiwanese manufacturers have lost their competitive advantages in cost production to international rivals; this impact is especially strong for small and medium sized enterprises (SMEs). Along with the theories and empirical evidence developed by previous scholars, this research examines the significant determinants of FDI practices and the timely entry of Taiwanese manufacturing SMEs. In addition, the case studies also provide a complete explanation of the forces perceived by these firms and the phenomena of their disproportionate level of FDI investments toward China as well as the demonstration of the real-world considerations and strategies employed by the firms beyond the associated literature. This research finds that low-cost labour, local market potential, network linkage, international experience, international managerial capability, psychic and cultural distance, political situation and institutions, and risks and language barriers are significant determinants of FDI commitments for Taiwanese manufacturing SMEs; while home country policy and attitude against investing in China are not determined to be significant in their decision-making processes. Moreover, the more international experience and managerial capability a Taiwanese manufacturer possesses, the less it considers psychic or cultural distances and language barriers as important host country factors. Finally, the different timing of FDI entry influences the manufacturer’s degree of concern about China’s market potential. This study could serve as a general guideline with important implications for Taiwanese manufacturing SMEs intending to engage in FDI in China or other emerging markets.